Mechanical Properties and Ballistic Performance for Different Coatings on HARDOX 450 Steel for Defense Applications - Nicolescu, Cosmin; Tiganescu, Tudor Viorel; Antoniac, Aurora; Iorga, Ovidiu; Ghiban, Brandusa; Pascu, Alexandru; Streza, Alexandru; Antoniac, Iulian (MDPI AG, 2025)
The aim of the current study is to investigate the mechanical properties and ballistic performance of HARDOX 450 steel for defense applications in different conditions: uncoated, alumina-coated, and LINE X polyurea-coated. Tensile tests and Vickers microhardness measurements were conducted, along with fracture surface analysis using stereomicroscopy, scanning electron microscopy, and computed tomography. Experimental results showed that uncoated HARDOX 450 steel exhibited the highest strength and hardness, with ductile fracture features. Polyurea-coated HARDOX 450 steel samples retained good mechanical properties and demonstrated effective ballistic protection, including the containment of fragments. In contrast, alumina-coated HARDOX 450 steel samples exhibited reduced strength and ballistic resistance, attributed to the microstructural changes in HARDOX 450 steel caused by the high-temperature deposition process of alumina. Numerical simulations performed with the 5.56 × 45 mm bullet used in the simulation, along with its ballistic impact interaction with the Hardox 450 target model, aligned well with experimental ballistic impact results for all the samples. Overall, LINE X polyurea coating on HARDOX 450 steel proved to be the more suitable coating for applications requiring a balance of mechanical strength and ballistic impact resistance.
Keywords: HARDOX 450 steel; coatings; alumina; LINE X polyurea; mechanical properties; ballistic impact